Respuesta :
Answer: C) 77
Remainder theorem: If p(x) is divided by (x-k), then the remainder is p(k)
In our case, p(x) = x^3-5x^2-4x+7 and k = 7
p(x) = x^3-5x^2-4x+7
p(7) = (7)^3-5(7)^2-4(7)+7
p(7) = 77
The remainder is 77
Side note: The nonzero remainder means x-7 is not a factor of x^3-5x^2-4x+7.
You can also use polynomial long division (see figure 1) or synthetic division (see figure 2). The figures are attached in the image below.
![Ver imagen jimthompson5910](https://us-static.z-dn.net/files/d84/9b6826b92597b474a71ab7f43e6176a8.png)
Answer:
C) 77
Step-by-step explanation:
Using remainder theorem:
x = 7
7³ - 5(7)² - 4(7) + 7
77